2022
DOI: 10.1097/ico.0000000000002998
|View full text |Cite
|
Sign up to set email alerts
|

KeraKlear Artificial Cornea Implantation Assisted by Femtosecond Laser in Eyes With Aniridia

Abstract: The purpose of this study was to evaluate the feasibility of treating aniridia-associated keratopathy with a nonpenetrating artificial cornea in 2 patients with corneal blindness secondary to aniridia.Methods: This was a prospective, nonrandomized, interventional study of 2 consecutive patients with corneal blindness caused by aniridia. Ophthalmological examination was performed before the nonpenetrating keratoprosthesis surgery and then repeated 1, 7, 15, 30, 90, and 180 days and subsequently every 90 days th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…All the included studies reported best corrected VAs, except for the study by Alio et al, 12 who did not specify whether it was best corrected or uncorrected, and for that by Vargas and Shiuey, 15 who reported uncorrected VA only. In addition, de Farias et al 16 did not report the exact VA in the period between the operation and 3 years thereafter, and one of their patients underwent phacoemulsification and Intraocular lens implantation surgery during the follow-up period. Alio et al, 12 on the other hand, only displayed the last follow-up VAs of patients who did not experience any complication (6 patients improved from light perception to counting fingers, 1 patient from light perception to hand motion, 1 patient from hand motion to counting fingers, and 1 patient from counting fingers at 10 cm to counting fingers at 2 m).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included studies reported best corrected VAs, except for the study by Alio et al, 12 who did not specify whether it was best corrected or uncorrected, and for that by Vargas and Shiuey, 15 who reported uncorrected VA only. In addition, de Farias et al 16 did not report the exact VA in the period between the operation and 3 years thereafter, and one of their patients underwent phacoemulsification and Intraocular lens implantation surgery during the follow-up period. Alio et al, 12 on the other hand, only displayed the last follow-up VAs of patients who did not experience any complication (6 patients improved from light perception to counting fingers, 1 patient from light perception to hand motion, 1 patient from hand motion to counting fingers, and 1 patient from counting fingers at 10 cm to counting fingers at 2 m).…”
Section: Resultsmentioning
confidence: 99%
“…One year after the operation, de Farias et al 16 reported a case of folding of the KK that was believed to be related to trauma. This Kpro needed to be replaced, and after that, no further complications were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110 ] A case report used partial thickness corneal incisions with ICRS software as an alternative method for drug delivery in nonresponding intrastromal infectious keratitis. [ 111 ] Other case reports use FSL-assisted intrastromal pockets to implant intrastromal KeraKlear artificial cornea in congenital aniridia[ 112 ] or insert silicon oil as palliative management of bullous keratopathy in blind eyes. [ 113 ]…”
Section: Other Proceduresmentioning
confidence: 99%